2018
DOI: 10.1016/j.ntt.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of pre- and postnatal co-use of cannabis and tobacco predict co-use and drug use disorders in adult offspring

Abstract: Co-use of cannabis and tobacco is increasingly common among women and is associated with tobacco and cannabis dependence and poorer cessation outcomes. However, no study has examined maternal patterns of co-use over time, or the impact of maternal co-use on co-use and drug problems in adult offspring. Pregnant women (M age = 23, range = 18-42; 52% African American, 48% White) were asked about substance use during each trimester of pregnancy, and at 8 and 18 months, 3, 6, 10, 14, 16, and 22 years postpartum. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 79 publications
(92 reference statements)
2
7
0
Order By: Relevance
“…Similarly, another study found that smaller head size, an increased risk of preterm birth and decreased birth weight in the neonates was associated with prenatal co-use of tobacco and cannabis compared to use of cannabis alone (Chabarria et al, 2016). With respect to childhood effects of co-use of tobacco and cannabis, offspring born to women who reported "decreasing couse" (i.e., primarily during prenatal and preschool periods) were more likely to be co-users themselves, and children of chronic co-users were more likely to have a substance use disorder, relative to those whose mothers reported no co-use or only postnatal co-use (De Genna, Goldschmidt, Richardson, Cornelius & Day, 2018). In addition, a recent study found that pre-and postnatal dual exposure increased secretory Immunoglobulin-A in early childhood relative to tobacco and cannabis-only exposure (Molnar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study found that smaller head size, an increased risk of preterm birth and decreased birth weight in the neonates was associated with prenatal co-use of tobacco and cannabis compared to use of cannabis alone (Chabarria et al, 2016). With respect to childhood effects of co-use of tobacco and cannabis, offspring born to women who reported "decreasing couse" (i.e., primarily during prenatal and preschool periods) were more likely to be co-users themselves, and children of chronic co-users were more likely to have a substance use disorder, relative to those whose mothers reported no co-use or only postnatal co-use (De Genna, Goldschmidt, Richardson, Cornelius & Day, 2018). In addition, a recent study found that pre-and postnatal dual exposure increased secretory Immunoglobulin-A in early childhood relative to tobacco and cannabis-only exposure (Molnar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, use of cannabis and tobacco products is prevalent among pregnant and postpartum individuals and may increase health risks for both the pregnant person and child (De Genna et al, 2019;Duko et al, 2023). Prior initial studies suggested that co-use of cannabis and tobacco may lead to greater likelihood of substance use in pregnancy or at postpartum (Coleman-Cowger et al, 2017;De Genna et al, 2018;England et al, 2020;Ko et al, 2020;Qato et al, 2020); results from the present study extend this literature by demonstrating that women who endorse prepregnancy co-use are less likely to achieve cessation during pregnancy and are more likely to relapse to use of cannabis/ tobacco into the postpartum period. It is notable that effects of couse were apparent after covarying for alcohol use and history of substance use problems.…”
Section: Use Of Tobacco and Cannabis In Pregnancymentioning
confidence: 99%
“…An emerging literature suggests that co-use of cannabis and tobacco may also be prevalent among pregnant and postpartum individuals. For example, among pregnant individuals, cannabis and tobacco co-use is up to three times more common than cannabisonly use (Coleman-Cowger et al, 2017;Ko et al, 2018), a majority of pregnant individuals who smoke cigarettes also report use of cannabis (Ko et al, 2015), and women who report co-use in pregnancy are more likely to continue using both or either substance during pregnancy or postpartum (Coleman-Cowger et al, 2017;De Genna et al, 2018;England et al, 2020;Ko et al, 2020;Qato et al, 2020). Use of tobacco or cannabis across the perinatal period is associated with numerous negative birth outcomes, such as low birth weight, premature birth, respiratory illness, cognitive deficits, and increased secondhand smoke exposure (Centers for Disease Control and Prevention, 2001;Duko et al, 2023;Lin et al, 2023;Regan et al, 2021), with co-use associated with worse neurobehavioral and birth outcomes (Coleman-Cowger et al, 2018;De Genna et al, 2019;Layoun et al, 2022;Stroud et al, 2018Stroud et al, , 2020.…”
mentioning
confidence: 99%
“…Substance use in the first year postpartum is further associated with depressive symptoms in mothers, infant exposure through breastfeeding and second hand smoke and other disruptions to parental care (Chapman & Wu, 2013; Forray, 2016; Herrmann, King, & Weitzman, 2008; Ko et al, 2018; Polcaro & Vettraino, 2020). In the longer term, parent substance use also increases risks of future substance use in offspring (Crume, 2019; De Genna, Goldschmidt, Richardson, Cornelius, & Day, 2018; Kerr, Capaldi, Pears, & Owen, 2012). For these reasons, guidelines in Australia and other countries recommend abstinence of substance use in pregnancy (Australian Government Department of Health, 2019; O'Keeffe et al, 2015).…”
mentioning
confidence: 99%
“…approximately 30% continue to drink alcohol at low levels) (Hutchinson, Moore, Breen, Burns, & Mattick, 2013; Muggli et al, 2016). Following childbirth, many women recommence use in the postpartum period (Borschmann et al, 2019; De Genna et al, 2018; Hutchinson et al, 2013). These trends make it pertinent to more precisely define who is most at risk of substance use in the perinatal period and when it is most effective to intervene.…”
mentioning
confidence: 99%